The relationships between parasite intensity, locomotor performance, and body condition in adult toads (Rhinella icterica) from the wild - Mretti, Eduardo H. [UNESP]; Madelaire, Carla B. [UNESP]; Silva, Reinaldo J. [UNESP]; Mendonca, Mary T.; Gomes, Fernando R. [UNESP] (Soc Study Amphibians Reptiles, 2014)
Most of the evidence for the deleterious effects of parasites on performance and body condition in their hosts results from experimental infection using one species of parasite. However, hosts in the field are normally infected by multiple parasite species present in different organs. We investigated the relationship between intensity of different parasites and several phenotypic characters of adult males of Rhinella icterica (Cururu Toad) captured in the field. We predicted that toads with higher parasite intensity would show lower locomotor performance, higher standard rates of oxygen consumption, poorer body-condition indices, and larger kidney, intestine, heart, lung, and liver masses. We found that these hosts were infected by six different species of parasites, with a dominance of monoxenous nematodes and no correlation between intensities of different parasites. Rhabdias fuelleborni was the only parasite associated with variation in a host's phenotype. Individuals of R. icterica with higher lung parasite intensity showed lower locomotor performance and had larger intestines and kidneys. Individuals with higher parasite intensity did not show poorer body condition or higher standard metabolic rates, suggesting that parasite intensity in the field was not associated with large changes in energy stores and that the relationship between parasite intensity and host performance remains nonsignificant during conditions of low energy demand.